Protective effect of Rheum turkestanicum root against mercuric chloride-induced hepatorenal toxicity in rats - Azar Hosseini; Arezoo Rajabian; Sahar Fanoudi; Mehdi Farzadnia; Mohammad Taher Boroushaki (Mashhad University of Medical Sciences, 2018)
Objective: The present study was designed to investigate the protective effects of hydroalcoholic extract of Rheum turkestanicum against HgCl2 hepatorenal toxicity in rats. Materials and Methods: Animals were randomly divided into five groups (n= 6 in each group) and received HgCl2 and plant's extract, intraperitoneally. Group1 received saline (1 mL/kg/day), group 2 received extract (200 mg/kg/day), group 3 was treated with HgCl2 (5 mg/kg/day,) and groups 4 and 5 received the extract (100 and 200 mg/kg/day, respectively), 1 hr before HgCl2 administration. All injections last for 3 days. Blood samples and specimens of the liver and kidney were collected 24 hr after the last injection. Results: Data showed that HgCl2 significantly increases liver malondialdehyde (MDA) level, reduces total sulfhydryl content and increases serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST) activity, compared to control group. The histopathological changes such as inflammatory cells infiltration was observed in HgCl2-treated group while plant's extract partially improved histological changes. The extract (100 and 200 mg/kg/day) improved the liver functions as reflected by significant reductions in AST and ALT levels in serum, MDA decreased and the content of total sulfhydryl elevated. Also, the extract improved necrosis and atrophy of the kidney induced byHgCl2. Pretreatment with the extract reduced creatinine and urea in serum, and glucose and protein concentrations in urine, compared to HgCl2- treated group (group III). The extract significantly reversed HgCl2-induced depletion in thiol content and elevation in MDA content. Conclusion: Therefore, oxidative stress may play an important role in HgCl2-induced hepatorenal injury and R. turkestanicum extract may be regarded as a useful to protect the kidney and liver against HgCl2-induced oxidative damage.